2006
DOI: 10.1159/000097072
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide Inhibits Endothelin-1 Production by Human Cultured Endothelial Cells: A New Vascular Action of This Endocannabinoid

Abstract: The endogenous cannabinoid receptor agonist anandamide (AEA) exerts vascular effects such as vasodilatation and hypotension. In this study, we determined the effect of AEA on endothelin-1 production by cultured human umbilical vein endothelial cells. Anandamide (≧5 µmol/l) significantly decreased endothelin-1 production in a dose-dependent manner, a response not affected by the specific CB1 receptor antagonist/inverse agonist SR-141716A. Adenosine, via activation of adenosine receptors (also targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…As stated previously, it has been shown that activation of cannabinoid CB 1 receptors leads to vasorelaxation and a decrease in vascular resistance . This vasorelaxation seems to be mediated via the nitric oxide as well as the endothelin system, both of which are known to also play an important role in the regulation of vascular tone in the eye . To what extend the latter findings can be translated to the ocular vasculature needs to be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…As stated previously, it has been shown that activation of cannabinoid CB 1 receptors leads to vasorelaxation and a decrease in vascular resistance . This vasorelaxation seems to be mediated via the nitric oxide as well as the endothelin system, both of which are known to also play an important role in the regulation of vascular tone in the eye . To what extend the latter findings can be translated to the ocular vasculature needs to be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…1) The activation of presynaptic CB1R is known to reduce neurotransmitter release and excitotoxicity in postsynaptic neurons (Marsicano et al,2003). 2) CB1R is involved in the regulation of vasodilation, both directly through vascular CB1R and indirectly through the inhibition of the vasoconstrictor endothelin‐1 (Ronco et al,2007). 3) CB1R regulates the release of proinflammatory factors such as nitric oxide (NO), IL‐1β, IL‐6, and TNF‐α (Fernandez‐Lopez et al,2006; Panikashvili et al,2006).…”
Section: Discussionmentioning
confidence: 99%
“…A cannabinoid derivative attenuated LPS-mediated microglial activation by inhibiting NF-jB signaling pathway (More et al 2013). Besides their anti-neuroinflammatory mechanisms, cannabinoids possess neuroprotective properties via diminishing excitotoxicity in postsynaptic neurons (Marsicano et al 2003), enhancing vasodilation through CB 1 in vascular smooth muscle, and the inhibition of endothelin-1 (Ronco et al 2007).…”
Section: Cannabinoidsmentioning
confidence: 99%